A design analysis for eco-fashion style using sensory evaluation tools: Consumer perceptions of product appearance. (November 2019) - Wagner, Melissa; Curteza, Antonela; Hong, Yan; Chen, Yan; Thomassey, Sebastien; Zeng, Xianyi
Abstract: Eco-designed fashion products can have a distinctive style in terms of environment-friendly appearance. In this study, an experimental design analysis process is proposed to help fashion designers in assessing consumers' perception of eco-style and ensure the success of sustainable product development. Our aim is to highlight the extent to which eco-fashion style exists in garment style. Since consumer perception towards ethical fashion is rather subjective, as human perception can be vague and full of uncertainty, we used sensory evaluation tools as well as the fuzzy logic method to process the data. We found that one can describe the garment style with eco-fashion descriptors based on the fuzzy logic analysis tool. The proposed experiment design process is applicable to the analysis of garment style regarding eco-fashion style and is able to distinguish the eco-products. Highlights: Eco-designed fashion products can have an environment-friendly appearance. Highlight the extent to which eco-fashion style exists in garment style with an experimental design analysis process. Sensory evaluation tools and the fuzzy logic method are used. Consumers tend to have a common perception between different garment styles and eco-fashion styles.